Artificially remediated plants impact soil physiochemical properties along the riparian zones of the three gorges dam in China - Naz, Farkhanda; Arif, Muhammad; Xue, Tan; Li, Changxiao (Frontiers in Forests and Global Change, 2024)
River ecosystem biodiversity and biogeochemical processes are shaped largely by riverside vegetation and soil. Moreover, river ecosystems provide ecological services influenced by the surrounding vegetation and soil interactions. However, the mechanisms by which artificially remediated plants (ARPs) and riparian soil interact to provide these benefits are still unclear among various ARPs. This study fills this gap and examines the impact of ARPs along the riparian zones of Three Gorges Dam (TGD) in Chongqing City, China. We sampled four varieties of ARPs from the Ruxi River Basin in the TGD. These varieties included Cynodon dactylon, Hemarthria altissima, Taxodium disticum, and Salix mastudana. Our results indicated substantial changes in soil physicochemical parameters. Comparably, T. distigum contains significantly higher soil chemical contents. Interestingly, principal component analysis explained almost 100% of the variance for all plant species in this study. Moreover, different vegetation types and soil chemical properties were positively correlated using Pearson correlation analysis (P < 0.05). Furthermore, all plant species exhibited strong negative correlations with physical characteristics (up to r = -1.00). Specifically, these mechanisms explain the interactions between ARPs and soil from riparian areas in the TGD. Hence, this study may facilitate ecological restoration and land management in degraded riparian areas.